The Current Status of Bacillus Calmette‐Guérin Vaccine Protective Efficacy - Patricia Méndez-Samperio (Vaccine Research, 2019)
The bacillus Calmette‐Guérin (BCG) vaccine against pulmonary tuberculosis (TB) remains with poor protective efficacy. However BCG is the only licensed vaccine against human TB. This review discusses the main research progress in the field of TB vaccine development and will summarize the current status, and main challenges for the development of a safer and more efficient TB vaccine.